PENGARUH DIET PUASA INTERMITTENT TERHADAP UREUM KREATININ PADA TIKUS PUTIH MODEL DIABETES MELITUS - Harahap, Huntari; Tarawifa, Susan; Syauqy, Ahmad; Justitia, Budi; Saputra, Ikmal Galih (LPPM Universitas Jambi, 2026)
ABSTRACT Diabetes Mellitus (DM) type 2 is a common metabolic disorder characterized by hyperglycemia. The most frequent microvascular complication in diabetes patients is diabetic nephropathy. Dietary management is one of the approaches in DM treatment. Intermittent fasting as a dietary intervention has been shown to improve overall health, weight management, blood pressure, and glomerular filtration rate (GFR). This study aims to investigate the effects of intermittent fasting on urea and creatinine levels in Wistar rats with a diabetes model. This study is a quantitative experimental analysis conducted in vitro in a laboratory setting, using a pretest and post-test group design. There was no difference in urea and creatinine levels before and after the intermittent fasting diet treatment in Wistar white rats. The one-way ANOVA and Kruskal-Wallis tests indicated no significant differences among the groups, as evidenced by the statistical test results with p-values > 0.05 (not significant). There was no difference in urea and creatinine levels before and after the intermittent fasting diet treatment in Wistar white rats. Keywords: Diabetes mellitus, intermittent fasting, urea, creatinine, white rats